Risk of COVID-19 related deaths for SARS-CoV-2 Omicron (B.1.1.529) compared with Delta (B.1.617.2) - Ward, IL; Bermingham, C; Ayoubkhani, D; Gethings, OJ; Pouwels, KB; Yates, T; Khunit, K; Hippisley-Cox, J; Banerjee, A; Walker, AS; Nafilyan, V (BMJ Publishing Group, 2022)
Objective: To assess the risk of COVID-19 death following infection from Omicron BA.1 relative to Delta (B.1.617.2).